Visualizing personalization on Instagram during the 2024 presidential election campaign - Pratiwi, Miftha; Andarini, Rindang Senja; Arianti, Yosi; Astuti, Misni (Program Studi Ilmu Komunikasi, 2025)
The digital era has transformed political communication by positioning social media, particularly Instagram, as a strategic platform for political actors to build personal branding and foster emotional connections with voters. However, academic studies on the use of visual strategies by presidential and vice-presidential candidates during political campaigns remain relatively limited. This study examines how Indonesia’s 2024 presidential and vice-presidential candidates used Instagram for personal branding, focusing on visual content to build voter support. Qualitative analysis of 2540 Instagram posts revealed three dominant dimensions of personal branding—style, competence, and standard—reflected in 15 themes, including public interaction, political campaigns, family orientation, achievements, and values. Results show that the style dimension — particularly public interaction and campaign activities — dominated image-building strategies, with candidate pair Anies Baswedan-Muhaimin Iskandar leading uploads in style and competence. At the same time, Ganjar Pranowo was strong in public interaction themes. Prabowo Subianto-Gibran Rakabuming emphasized achievements, cultural themes, and the celebration of memorable moments. These findings demonstrate that Instagram visuals were strategically used to highlight uniqueness, strengthen credibility, and foster emotional resonance with voters, underscoring the central role of visual branding in influencing voter behavior.